Facing facts using the library director, David Newman ; writers, Donald Hamilton, David Newman ; producer, Dennis Sawyer - Hamilton, Donald; Newman, David; Sawyer, Dennis ([Montreal] National Film Board of Canada)
Shows the importance and use of the library as a source of information and knowledge.
VHS
Facing facts (13 min.) -- Using library (6 min.) -- Bridging (16 min.) -- Accomodation library (30 min.)
Keywords: Libraries and readers; Library science